KOMPETENSI SPIRITUAL GURU SEBAGAI KEKUATAN PEDAGOGIS TRANSFORMASIONAL DALAM PENGUATAN MODERASI BERAGAMA DI MADRASAH - Ahmad Fuad Bahalwan; Ha’niatul Khoiroh (Journal Multicultural of Islamic Education, 2025)
This study examines the role of teachers’ spiritual competence as a foundational pillar in strengthening religious moderation values among students at Madrasah Aliyah Al Ibrahimy Konang Bangkalan. The research addresses the growing need for moderate Islamic education within Indonesia’s diverse social and religious context. Using a qualitative case study approach, data were collected through in-depth interviews, non-participatory observations, and documentation. The findings reveal that spiritual competence shapes the entire pedagogical process through five interconnected stages: identification of students’ initial values, integration of moderation principles into classroom instruction, teachers’ daily moral exemplification, habituation of religious practices, and systematic evaluation and reflection. These processes significantly influence students’ attitudes, particularly in developing tolerance, respectful communication, emotional maturity, and harmonious social interaction. The study concludes that teachers’ spiritual competence is not only a pedagogical asset but also a transformative force that nurtures students’ intellectual, moral, and spiritual development. This research contributes to strengthening theoretical insights into spiritual pedagogy and provides practical implications for enhancing moderate Islamic education in contemporary madrasah settings.